MUC expression in adenosquamous carcinoma of the head and neck regions of Japanese patients: Immunohistochemical analysis. (March 2014) - Kusafuka, Kimihide; Muramatsu, Koji; Iida, Yoshiyuki; Mori, Keita; Miki, Tomoko; Suda, Toshihito; Fuke, Tomohito; Kamijo, Tomoyuki; Onitsuka, Tetsuro; Nakajima, Takashi
<x xml:space="preserve">Abstract</x> Adenosquamous carcinoma (ASC) is a rare malignant neoplasm of the head and neck regions. We elucidated the relationship between ASC and MUC molecule expression. We selected 14 cases of ASC in the head and neck, and examined them immunohistohcmically. Seven cases of tongue, 3 cases of larynx and 4 cases of hypopharynx carcinoma were selected. Nine (64.3%) of 14 cases showed lymph node metastasis at the diagnosis. Laryngeal and hypopharyngeal cases showed a higher stage. Six cases (66.7%), all of which showed lymph node metastases, died of disease. Immunohistochemical examinations showed that ASC was positive for both markers of squamous cell carcinoma and adenocarcinoma. ASC showed positivity for MUC1 (13 cases: 92.3%), MUC1core (12 cases: 85.2%) and MUC4 (12 cases: 85.7%). In rare ASC of the head and neck region, it was revealed that MUC1 and MUC4 expression might be associated with its nodal status.